The disengagement process among young athletes when withdrawing from sport: A new research approach - Eliasson, I.; Johansson, A. (International Review for the Sociology of Sport, 2021)
The reasons young athletes drop out of sport have eluded scientists and sport organizations for many decades. Despite a large body of research on the subject, unanswered questions remain. This article reports on a new research approach that analyses sport withdrawal as a process. The study draws on Ebaugh`s sociological theory of disengagement and is based on data from semi-structured interviews with 12 girls aged 12 to 17 and 12 of their parents. By studying withdrawal from sport as a process, we found that the reasons comprise a combination of several salient interplaying factors related to changes. Organizational changes in sport and changes in the young athletes` overall lives, together with changes in normative cultural and individual expectations associated with the young athlete role, are decisive for these girls to withdraw from sport. Furthermore, the disengagement process may be fairly long and emotional for young athletes, and less reversible the further into the process they progress.